Chemical and electrical properties of (NH4)2S passivated GaSb surface*Project supported by the National Natural Science Foundation of China (No. 61474104). (July 2015) - Tao, Dongyan; Cheng, Yu; Liu, Jingming; Su, Jie; Liu, Tong; Yang, Fengyun; Wang, Fenghua; Cao, Kewei; Dong, Zhiyuan; Zhao, Youwen
Abstract The surface chemical properties of gallium antimonide (GaSb) after ammonium sulfide ((NH4)2S) solution passivation have been studied by X-ray photoelectron spectroscopy (XPS), time of flight secondary ion mass spectroscopy (TOF-SIMS) and I–V measurement. An advantage of neutral (NH4)2S + S solution over pure (NH4)2S solution and alkaline (NH4)2S + S solution has been found in the ability to passivate the GaSb surface by contrast and comparison. It has been found that alkaline (NH4)2S + S solution passivation effectively removes oxides of the GaSb surface and forms sulfide products to improve device performance. TOF-SIMS complementally demonstrates that pure (NH4)2S passivation did form sulfide products, which are too soluble to really exist. The lowest roughness determined using a 3D optical profilometer and the highest improved SBD quality proved that neutral (NH4)2S + S solution passivation worked much better in improving the surface properties of GaSb.